Studi Pengaruh Variasi Bed Material Pasir Besi Terhadap Efisiensi Pembakaran Fluidized Bed Limbah Medis - Situmorang, Daniel Mual Aprio; Winaya, I Nyoman Suprapta; Wijaksana, Hendra (Teknik Desain Mekanika; Vol 10 No 3 (2022): Juli 2022 : Teknik Desain Mekanika, 2022)
Abstractt Medical waste treatment is one of the many complex and formidable challenges. As the grows of world's population, the demand for more qualified medical services increases. Incineration is a commonly used method for treating medical waste. In this study, what is known as a fluidized bed incinerator is used as the combustion medium. This study uses medical waste as fuel. Before using this medical waste as fuel, it must be treated first. Used medical waste will first be chopped, mixed and tested to determine the characteristics and content of the medical waste. This study was conducted using a fluidized bed combustion prototype designed for research scale combustion. Based on the tests carried out, data were obtained in the form of medical waste mass, ash mass, combustion time, exhaust gas content and calorific value. And from that, the Combustion Efficiency will be obtained on the fluidized bed of medical waste using a variety of iron sand bed material. It can be concluded that iron sand with a diameter variation of 0.2 has the highest efficiency value of 95.742%, compared to a variation of iron sand with a diameter of 0,8 mm, 1,1 mm and 0,5 mm which respectively have a value of 91,095 %, 94,478% and 95,205%. Keywords: Efficiency, Fludized Bed, Medical Waste, Combustion, Iron Sand